The Obamas and a (post) racial America? - Parks, Gregory, 1974-; Hughey, Matthew W. (Matthew Windust) (Oxford : Oxford University Press, 2011)
Looking beyond public behaviours and how people describe their own attitudes, the contributors draw from the latest research to show how, despite the Obama family's rapid rise to national prominence, many Americans continue to harbour unconscious, anti-black biases.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States -- Race relations; African Americans -- Social conditions -- 21st century; Racism -- United States; Post-racialism -- United States; Obama, Barack -- Influence; Obama, Michelle, -- 1964- -- Influence